2020
DOI: 10.1108/ejm-08-2018-0522
|View full text |Cite
|
Sign up to set email alerts
|

The bright and dark sides of humorous response to online customer complaint

Abstract: Purpose Displaying a sense of humour provides various interpersonal benefits including reducing tension and promoting conflict resolution, but should a firm use humour in response to publicly viewable online customer complaints after a service failure? The purpose of this study is to demonstrate that a firm’s use of humour in response to negative online consumer reviews has both positive and negative effects on perceptions of corporate image from a customer-as-onlooker perspective. Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 116 publications
3
33
0
Order By: Relevance
“…Therefore, the current study broadens our understanding of how humor operates in a non-traditional approach. The present research also contributes to the humor literature, which suggests the importance of using humor that is relevant to the message context, such as humorously written replies to customer complaints ( Shin and Larson, 2020 ). Our work also provides insight into the way email correspondence uses humor, as an interpersonal resource for leaders to influence followers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, the current study broadens our understanding of how humor operates in a non-traditional approach. The present research also contributes to the humor literature, which suggests the importance of using humor that is relevant to the message context, such as humorously written replies to customer complaints ( Shin and Larson, 2020 ). Our work also provides insight into the way email correspondence uses humor, as an interpersonal resource for leaders to influence followers.…”
Section: Discussionmentioning
confidence: 74%
“…It was recently suggested that humorous text messages may be an effective tool for shaping beneficial organizational image. Shin and Larson (2020) conducted three experimental marketing studies suggesting that humorous responses to a client’s complaints by a service agent have a favorable influence on the firm’s perceived attractiveness, regardless of the type of humor used (i.e., affiliative or aggressive humor) The impact of humorous emails on employees’ willingness to work with managers has not been examined previously, and only a few leadership research studies have examined the contribution of managers’ humorous expression and employees’ behavioral intentions. However, we suggest that employees might positively evaluate written humorous messages sent by their managers via email correspondence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of Ngapak language with humor can be an asset to build a positive government image so the public believes agencies can be trusted to receive a variety of complaint styles. Even so, an organization must pay attention to funny replies to complainants or complaints (Shin & Larson, 2020).…”
Section: Complaint Systemmentioning
confidence: 99%
“…Potential complainants may observe these interactions, to ascertain how or when the firm will intervene, as some customers consider VPO behaviour to be within the control of the firm and hold expectations that the firm will take responsibility and manage those consumer-to-consumer discourses (Colm et al, 2017). Potential complainants may also observe these multilogues to predict whether such social discourse will be favourable or unfavourable in the event that they proceed with EJM 56,1 posting their own complaint (Shin and Larson Lindsay, 2020;Weitzl and Hutzinger, 2017).…”
Section: Introductionmentioning
confidence: 99%